2004
DOI: 10.1016/j.otohns.2004.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Fungal Sinusitis: Can We Predict the Recurrence?

Abstract: At the present time, it is not possible to predict recurrence using parameters of age, sex, extent of disease, and serum IgE levels. Larger number of patients preferably in a prospective multicenter meta study are required to address this issue. Though use of systemic corticosteroid does not decrease the incidence of recurrence, it may delay the onset of recurrence and decrease the severity of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Unilateral presentation was high in our study similar to studies by Bent & Kuhn 15 Sohail et al 16 and Thahim et al 10 Intra op findings were extensive nasal polyposis with thick mucin which was of pea nut butter appearance were present. The debrided tissue was sent for HPE which showed fungal hyphae, eosinophils, charcot laden crystals in all cases.…”
Section: Discussionsupporting
confidence: 90%
“…Unilateral presentation was high in our study similar to studies by Bent & Kuhn 15 Sohail et al 16 and Thahim et al 10 Intra op findings were extensive nasal polyposis with thick mucin which was of pea nut butter appearance were present. The debrided tissue was sent for HPE which showed fungal hyphae, eosinophils, charcot laden crystals in all cases.…”
Section: Discussionsupporting
confidence: 90%
“…In a study of 44 patients with AFS [26], CT scans showed involvement of three or more sinuses in all patients. Both unilateral [35, 38] and bilateral [8, 34, 39] predominance of the disease was noticed in different series. Mukherji et al [36] retrospectively reviewed CT scans, along with surgical and histologic reports, in 45 patients with AFS and found an almost equal preponderence of unilateral (49%) and bilateral involvement (51%).…”
Section: Introductionmentioning
confidence: 99%
“…Our recurrence rate of 20% is lower than the average rate in current literature. 19 The 2 patients in this series that required reoperation were allergic to all 6 of the common fungal allergens, and 1 of these patients was started on SLIT prior to surgery. As noted previously, Ferguson 18 has recognized initiation of immunotherapy prior to surgery as a risk factor for treatment failure.…”
Section: Discussionmentioning
confidence: 92%